Flexural Strengthening of Reinforced Concrete Beams with Externally Side-Bonded CFRP Laminates - Salama, Ahmad S. D. (2016)
A Master of Science thesis in Civil Engineering by Ahmad S. D. Salama entitled, "Flexural Strengthening of Reinforced Concrete Beams with Externally Side-Bonded CFRP Laminates," submitted in April 2016. Thesis advisor is Dr. Rami Hawileh and thesis co-advisor is Dr. Jamal A. Abdalla. Soft and hard copy available.